SDG14 - life below water : towards sustainable management of our oceans - Pandey, Umesh Chandra; Nayak, Subash Ranjan; Roka, Krishna; Jain, Trilok Kumar (Concise guides to the United Nations Sustainable Development Goals., 2021)
'SDG14 - Life below water: towards sustainable management of our oceans' describes the dependence of human beings on shore and marine resources and highlights how oceanic life sustains the livelihoods of people living in coastal areas, affects global economy and plays a significant role for making earth habitable. Chapters give accounts of human interventions on oceanic life and demonstrate the various ways in which the sustainability of the oceanic system is threatened. Looking to sustainable management and protection of marine and coastal ecosystems, chapters investigate best practices initiated in different countries, address issues such as overfishing and the legal framework for conservation and sustainable use of oceans and their resources. Concise Guides to the United Nations Sustainable Development Goals comprises 17 short books, each examining one of the UN Sustainable Development Goals. The series provides an integrated assessment of the SDGs from economic, legal, social, environmental and cultural perspectives.